Can social support alleviate inflammation associated with childhood adversities?. (1st February 2014) - Runsten, Silja; Korkeila, Katariina; Koskenvuo, Markku; Rautava, Päivi; Vainio, Olli; Korkeila, Jyrki
Abstract: Objective: Childhood adversities have been linked to elevated high-sensitivity C-reactive protein (hsCRP), which has been associated with increased morbidity. Low social support has been reported to worsen the prognosis in heart disease and cancer, and high social support has been linked to lower hsCRP. We hypothesized that social support could be a mediating factor between childhood adversities and hsCRP. Methods: The sample was drawn from the data of the nationwide Health and Social Support Study (HeSSup Study) to which 25, 898 Finns had responded in 1998. The cohort was stratified into groups of high and low social support, and the study group consisted of 100 women in both groups. Additionally, we invited a randomly drawn group of 50 subjects and a group of 62 women who had reported depressive symptoms. Of the 312 women, 116 participated in the study. Results: Social support score (Social Support Questionnaire, SSQ) was lower when the number of adverse experiences in childhood was high ( r = − 0.251, P = 0.007). hsCRP and SSQ were inversely associated ( r = − 0.188, P = 0.046). In the adjusted general linear model, the level of social support was significantly associated with hsCRP and there was a statistically significant interactive effect of small effect size of childhood adversities and the level of social support on hsCRP (ES = 0.123, P = 0.004). Conclusion: This finding suggests that childhood adversity may affect social relationships and that high social support may attenuate the health risks caused by childhood adverse experience.